Anterolateral thigh free flap- largest size flap till date in lateral skull base defect reconstruction: an interesting case report - Gupta, Madhusoodan; Saleem, Abid; Kaladagi, Raghavendra; Singh, Pradeep K.; Chandra, Rohit; Johar, Manoj K.; Varshney, Deepti; Biswkarma, Vishal K. (International Surgery Journal, 2021)
Vascularised free tissue transfer has revolutionized skull base defect reconstruction. It allows to restores form and functions without compromising the principles of oncoplastic surgery. Anterolateral thigh (ALT) free flap is a workhorse flap in head and neck reconstruction. The versatility of the ALT-free flap makes it unique to reconstruct almost every soft-tissue defect in head and neck reconstruction. Due to the large surface of the anterolateral thigh, a very large flap can be harvested with very little donor site morbidity. Here we have reported a case of 40 years, male patient, with a known case of primary squamous cell carcinoma (SCC) of the left parotid gland. After the surgical extirpation of the tumor, an extensive soft-tissue defect was created in the region of the left lateral skull base defect. For coverage of large defect, we did the ALT free flap size 25×18 cm (450 cm2). The donor site was partially closed primarily and partially skin grafted. The patient was discharged uneventfully on the 7th postoperative day.